Evaluation of energy intake compared with indirect calorimetry requirements in critically ill patients with acute brain injury. Issue 5 (9th November 2021) - May, Casey C.; Harris, Emily A.; Hannawi, Yousef; Smetana, Keaton S.
Abstract: Background: Nutrition support in critically ill patients with acute brain injury is vitally important because of known hypermetabolism. We aimed to describe energy and protein intake within the first 72 h in a broad neurocritical care population and compare energy intake with the indirect calorimetry (IC) resting energy expenditure (REE) target. Methods: IC data, daily energy, and protein intake were collected through chart review over the first 7 days of hospital admission. We evaluated the type and amount of tube‐feed product received, volume of propofol (1.1 kcal/ml) and clevidipine (2 kcal/ml), and amount of supplemental protein received. Results: Ninety‐one patients were included, with the majority presenting with either intracerebral hemorrhage (35.2%) or acute ischemic stroke (26.4%). The median day of admission on which IC was completed and enteral nutrition was initiated was day 3 (2–5) and day 1 (1–2), respectively. The difference in kilocalories received compared with IC REE target within the first 72 h was significantly different (2831 kcal [1663–4072] vs 4275 kcal [3450–5811]; Z = −6.469; P < .001). The median kilocalories received as tube feeds during the first 72 h was 88% (55%–99%), and the mean protein received in the first 72 h was 0.7 ± 0.5 g/kg/day. Conclusion: In this population, patients had lower energy intake compared with their energy needs determined by IC during the first 72 h of admission but attained 7‐day goals. Future studies should investigate barriers to improve energy delivery in this patient population.